Humanistic training for dental students and professionals: a forgotten dimension - Marcucci, Marcelo (2023)
Humanities include knowledge about arts, literature, and human sciences focused on the area of health, which emerged as a counterpoint to excessive health technologization of health. The assumption is to help health professionals develop beyond technical knowledge, supported by human sciences and humanities, in interacting with the patient in all dimensions: spiritual, ethical, psychic, cultural, and social. This literature review reflects on the importance of the Humanities for the performance of dental surgeons, highlighting some paths for its development. The article search strategy was A convenience sample from three databases (LILACS, PubMed, and SciELO) and excerpts from books on the subject from 1995 to 2021 was adopted as the article search strategy. The discussion on the Humanities is more advanced in the medical field, with initiatives in undergraduate curricula and space in some scientific journals. In dentistry, the topic is still little discussed in educational institutions and continuing professional education. In Brazil, some groups such as the Center of Health Sciences History and Philosophy (CeHFi) of the Federal University of São Paulo (Unifesp), are developing pioneering work with health students involving the reflective reading of classic literature. No records of similar initiatives were found specifically in the dental area. More studies in the context of dentistry are needed to increase knowledge on the subject.